Nonprofits in urban America - Hula, Richard C., 1947-; Jackson-Elmoore, Cynthia, 1965- (Quorum Books, 2000)
A study of the role of non-profits in local governing coalitions; the potential of non-profits to replace social welfare programmes; their efforts to restructure elements of the local political process; and the impacts of the changing roles of non-profit organizations in the urban community.